A Genetic Algorithm NURBS-based new approach for fast kinematic limit analysis of masonry vaults. (1st April 2017) - Chiozzi, Andrea; Milani, Gabriele; Tralli, Antonio
Highlights: From the NURBS 3D model of a generic masonry vault to a rigid body assembly. Kinematic limit analysis based on a homogenized upper bound formulation. Dissipation allowed along element edges only. Optimization of the rigid body assembly through a suitable Genetic Algorithm. Fast determination of the load bearing capacity and failure mechanism of the masonry vault. Abstract: The present paper proposes a new Genetic Algorithm NURBS-based approach for the limit analysis of masonry vaults based on an upper bound formulation. A given masonry vault geometry can be represented by a NURBS (Non-Uniform Rational B-Spline) parametric surface and a NURBS mesh of the given surface can be generated. Each element of the mesh is a NURBS surface itself and can be idealized as a rigid body. An upper bound limit analysis formulation, which takes into account the main characteristics of masonry material is deduced, with internal dissipation allowed exclusively along element edges. The approach is capable of well predicting the load bearing capacity of any masonry vault of generic shape. It is proved that, even by using a mesh constituted by very few elements, a good estimate of the collapse load multiplier is obtained provided that the initial mesh is adjusted by means of a meta-heuristic approach (i.e. a Genetic Algorithm, GA) in order to enforce that element edges accurately represent the actual failure mechanism. The proposed method turns out to be both accurate and much less computationally expensive than existing methods for the limit analysis of masonry vaults.